2013
DOI: 10.5603/piap.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Selected Factors on the Attendance of the High-Risk Population in the Early Lung Cancer Detection Program

Abstract: The influence of selected factors on the attendance of the high-risk population in the early lung cancer detection program Analiza czynników wpływających na zgłaszanie się osób zagrożonych zachorowaniem na raka płuca do programu wczesnego wykrywaniaThe authors declare no financial disclosure AbstractIntroduction. Lung cancer is the most common cause of cancer-related death worldwide, killing almost 22,000 people in Poland every year. Low-dose computed tomography (LDCT) is the most promising tool of secondary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, one large study from the UK of a LDCT screening was included in this review [ 11 ]. Several studies from various European countries with a focus on LDCT screening were also included in this review: Denmark using data from the Danish Lung Cancer Screening Trial including 4101 participants [ 25 ], France with 765 participants [ 26 ], Italy with ITALUNG and its 3206 participants [ 27 ], the Netherlands and Belgium with 5161 participants [ 19 ], and one study from Poland with 1619 participants [ 28 ]. Except for the French and Italian studies, all of the included European studies used a measurement of social status.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one large study from the UK of a LDCT screening was included in this review [ 11 ]. Several studies from various European countries with a focus on LDCT screening were also included in this review: Denmark using data from the Danish Lung Cancer Screening Trial including 4101 participants [ 25 ], France with 765 participants [ 26 ], Italy with ITALUNG and its 3206 participants [ 27 ], the Netherlands and Belgium with 5161 participants [ 19 ], and one study from Poland with 1619 participants [ 28 ]. Except for the French and Italian studies, all of the included European studies used a measurement of social status.…”
Section: Resultsmentioning
confidence: 99%
“…The widespread underuse of lung cancer screening is a result of multilevel barriers to healthcare utilization. Previous studies suggested that people without insurance coverage, young adults, adults with low awareness of cancer screening, African Americans, Hispanics, and married adults are less likely to have preventive lung cancer screenings (Zakrzewska et al , 2013; Cardarelli et al , 2017; Lee et al , 2020; Williams et al , 2020). However, hypothesis-driven models (e.g.…”
Section: Introductionmentioning
confidence: 99%